CONTRIBUTION OF PERSONALITY, AND LEADERSHIP TO ORGANIZATIONAL COMMITMENT OF THE UNIVERSITY OF MH.THAMRIN JAKARTA - Mansur , Mansur (Dinasti International Journal of Digital Business Management, 2020)
This study aims to determine the magnitude of the contribution of personality and leadership to the organizational commitment of lecturers. This research method is survey research. The subjects of this study were 80 lecturers randomly taken at MH. Thamrin UniversityJakarta.Data were collected using a questionnaire instrument using a Likert scale. The validity of the data is obtained by testing the validity and reliability; all data have a normal distribution. The results showed that personality contributed significantly to the organizational commitment of lecturers. Likewise, leadership provides a contribution significant to the organizational commitment of lecturers. The coefficient of determinationis personality and leadership that has a moderate relationship to the organizational commitment of lecturers.